Villainy in France (1463-1610) - Patterson, Jonathan (Oxford University Press, 2021)
This volume explores the idea of villainy as a literary trope in French literature from 1450 to 1610, and the extent to which conceptions of villainy portrayed in the works of a number of well known and unfamiliar French writers came to influence representations of the villain in English settings.
10.1093/oso/9780198840015.001.0001
Keywords: French literature; Criminal law; Villains in literature; Criminals in literature; Crime in literature; Law and literature